Comparison of liver biochemical abnormality between COVID-19 patients with liver cirrhosis versus COVID-19 alone and liver cirrhosis alone: A STROBE observational study. Issue 19 (14th May 2021) - An, Yang; Ma, Zhuang; Guo, Xiaozhong; Tang, Yufu; Meng, Hao; Yu, Hao; Peng, Chengfei; Chu, Guiyang; Wang, Xinwei; Teng, Yue; Zhang, Quanyu; Zhu, Tianyi; et al.
Abstract : Abstract: Coronavirus disease (COVID-19) patients frequently develop liver biochemical abnormality. However, liver biochemical abnormality in COVID-19 patients with liver cirrhosis is under-recognized. Patients hospitalized during COVID-19 pandemic in China (ie, from February to April 2020) were screened. All of 17 COVID-19 patients with liver cirrhosis consecutively admitted to the Wuhan Huoshenshan Hospital were identified. Meanwhile, 17 age-, sex-, and severity-matched COVID-19 patients without liver cirrhosis admitted to this hospital were selected as a control group; all of 14 cirrhotic patients without COVID-19 consecutively admitted to the Department of Gastroenterology of the General Hospital of Northern Theater Command were selected as another control group. Incidence of liver biochemical abnormality and decompensated events were primarily compared. Among the COVID-19 patients with liver cirrhosis, the incidence of liver biochemical abnormality at admission and during hospitalization were 76.50% and 84.60%, respectively; 7 (41.20%) had decompensated events at admission; 1 was transferred to intensive care unit due to gastrointestinal bleeding. Among the COVID-19 patients without liver cirrhosis, the incidence of liver biochemical abnormality at admission and during hospitalization were 58.80% ( P = .271) and 60.00% ( P = .150), respectively. Among the cirrhotic patients without COVID-19, the incidence of liver biochemical abnormality at admission and during hospitalization were 69.20% ( P = .657) and 81.80% ( P = .855), respectively; 11 (78.60%) had decompensated events at admission ( P = .036). None died during hospitalization among the three groups. Liver biochemical abnormality is common in COVID-19 patients with liver cirrhosis. Management of decompensated events in cirrhotic patients without COVID-19 should not be neglected during COVID-19 pandemic.